2016
DOI: 10.1080/17843286.2016.1159797
|View full text |Cite
|
Sign up to set email alerts
|

The association of neutrophil/lymphocyte ratio and platelet/lymphocyte ratio with clinical outcomes in geriatric patients with stage 3–5 chronic kidney disease

Abstract: The neutrophil/lymphocyte ratio predicts all-cause of mortality in geriatric patients with chronic kidney disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
21
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 29 publications
5
21
2
Order By: Relevance
“…Studies have reported a close association between the worsened prognosis and complications of cardiovascular, metabolic, malignant, and inflammatory diseases and NLR (Corriere et al, 2018;Li et al, 2017;Akbas et al, 2014;Ulu et al, 2013;Jiang et al, 2018;Polat et al, 2017;Uysal et al, 2016;Kalay et al, 2012;Xiao et al, 2014;Wei et al, 2014). In addition, NLR is stated to be a new inflammatory marker for cardiovascular risk and cardiac mortality (Uysal et al, 2016;Tatar et al, 2016). It has reported that NLR can be used as a parameter predicting mortality in end stage renal failure (Tatar et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have reported a close association between the worsened prognosis and complications of cardiovascular, metabolic, malignant, and inflammatory diseases and NLR (Corriere et al, 2018;Li et al, 2017;Akbas et al, 2014;Ulu et al, 2013;Jiang et al, 2018;Polat et al, 2017;Uysal et al, 2016;Kalay et al, 2012;Xiao et al, 2014;Wei et al, 2014). In addition, NLR is stated to be a new inflammatory marker for cardiovascular risk and cardiac mortality (Uysal et al, 2016;Tatar et al, 2016). It has reported that NLR can be used as a parameter predicting mortality in end stage renal failure (Tatar et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, NLR is stated to be a new inflammatory marker for cardiovascular risk and cardiac mortality (Uysal et al, 2016;Tatar et al, 2016). It has reported that NLR can be used as a parameter predicting mortality in end stage renal failure (Tatar et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Tatar et al [30] found the basal NLR was an independent predictor of death in geriatric patients with stage 3–5 chronic kidney disease. Kocyigit et al [31] demonstrated that patients with a high NLR had worse prognosis and significantly faster progression to the dialysis compared with those with a low NLR.…”
Section: Discussionmentioning
confidence: 99%
“…NLR and PLR are current markers of interest for systemic inflammation (11)(12)(13). Data is limited in patients with cHepC.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophil lymphocyte ratio (NLR) and thrombocyte lymphocyte ratio (PLR) are used as markers of inflammation in various diseases including atherosclerotic heart and renal disease. They are more sensitive compared to total leukocyte counts (11)(12)(13). However, there are no data to confirm their use in cHepC patients.…”
Section: Introductionmentioning
confidence: 99%